Understanding of COVID-19 vaccination in pregnant female – Hesitancy and acceptance: A prospective observational study - Parul Singh; Meenakshi Chauhan; Verma, Menka; Vani Malhotra; Sushila Chaudhary; Ruchi Yadav (Asian Journal of Medical Sciences, 2022)
Background: India is one of the most severely affected countries due to the COVID-19 pandemic. A higher risk of severe illness and complications from COVID-19 had been observed in pregnant women as compared to nonpregnant women. The government of India on July 2, 2021, provided approval for the vaccination of pregnant women against COVID-19. A little data regarding the safety or harm during pregnancy of vaccination were available that time. Lack of safety data, fear, mistrust, underestimation of efficacy of vaccine, and chaos due to pandemic makes indecisive surrounding for pregnant women and this causes hesitancy with decision making about the COVID-19 vaccination. Aims and Objectives: This study aims to analyze the willingness and hesitancy of pregnant women to get vaccinated against COVID-19. Materials and Methods: This prospective study was conducted in a tertiary care institute in Northern India. Five hundred antenatal women who were eligible for COVID-19 vaccination were included in this study. Informed consent has been taken and data were analyzed after filling face to face questionnaire regarding vaccine acceptance or hesitancy. Results: The present study revealed low acceptance of COVID-19 vaccination in pregnancy. Prime reasons for the same are no allowance by the family and the possibility of vaccine harming the baby. Conclusion: Specific efforts should be directed toward high-risk populations including pregnant women and those who are planning for pregnancy. This will promote vaccination rates by increasing people’s trust in immunization and the health-care system.